The effects of aging in the hippocampus and cognitive decline - Bettio, Luis E.B.; Rajendran, Luckshi; Gil-Mohapel, Joana (Neuroscience and biobehavioral reviews, 2017)
[Display omitted] •A reduction in hippocampal volume may contribute to age-related cognitive decline.•Age-related hippocampal atrophy results from neuronal loss and impaired neurogenesis.•Neuroinflammation and reduced trophic support cause age-related cognitive decline.•Cellular, epigenetic and plastic changes underlie hippocampal dysfunction with age.•Lifestyle modifications can delay the deleterious effects of aging on the hippocampus. Aging is a natural process that is associated with cognitive decline as well as functional and social impairments. One structure of particular interest when considering aging and cognitive decline is the hippocampus, a brain region known to play an important role in learning and memory consolidation as well as in affective behaviours and mood regulation, and where both functional and structural plasticity (e.g., neurogenesis) occur well into adulthood. Neurobiological alterations seen in the aging hippocampus including increased oxidative stress and neuroinflammation, altered intracellular signalling and gene expression, as well as reduced neurogenesis and synaptic plasticity, are thought to be associated with age-related cognitive decline. Non-invasive strategies such as caloric restriction, physical exercise, and environmental enrichment have been shown to counteract many of the age-induced alterations in hippocampal signalling, structure, and function. Thus, such approaches may have therapeutic value in counteracting the deleterious effects of aging and protecting the brain against age-associated neurodegenerative processes.